2014
DOI: 10.1124/dmd.114.060350
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Metabolism in Human Skin: Skin Explants Show Full Coverage for Glucuronidation, Sulfation,N-Acetylation, Catechol Methylation, and Glutathione Conjugation

Abstract: Although skin is the largest organ of the human body, cutaneous drug metabolism is often overlooked, and existing experimental models are insufficiently validated. This proof-of-concept study investigated phase II biotransformation of 11 test substrates in fresh full-thickness human skin explants, a model containing all skin cell types. Results show that skin explants have significant capacity for glucuronidation, sulfation, N-acetylation, catechol methylation, and glutathione conjugation. Novel skin metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 65 publications
1
40
0
2
Order By: Relevance
“…It is known that phase II metabolism (conjugation) does occur in human skin [58]. In fact, the use of skin explants demonstrated full coverage for glucuronidation, sulfation, N -acetylation, catechol methylation and glutathione conjugation, and investigators and cosmetic companies have explored the applications of natural compound analogs to address this issue [57,58,59].…”
Section: Human Skin Gene Expressionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that phase II metabolism (conjugation) does occur in human skin [58]. In fact, the use of skin explants demonstrated full coverage for glucuronidation, sulfation, N -acetylation, catechol methylation and glutathione conjugation, and investigators and cosmetic companies have explored the applications of natural compound analogs to address this issue [57,58,59].…”
Section: Human Skin Gene Expressionmentioning
confidence: 99%
“…In fact, the use of skin explants demonstrated full coverage for glucuronidation, sulfation, N -acetylation, catechol methylation and glutathione conjugation, and investigators and cosmetic companies have explored the applications of natural compound analogs to address this issue [57,58,59]. However, the conjugation enzymatic activities in human skin are in the pmol/mg skin/h range.…”
Section: Human Skin Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Manevski et al (2015) reported for human skin N-acetylation for the first time for procainamide as substrate. Of totally 11 substrates for 5 xenobiotic conjugating enzyme activities the highest observed activity was N-acetylation of para-toluidine.…”
Section: Introductionmentioning
confidence: 99%
“…SIRT1: NAD-dependent deacetylase sirtuin-1 or silent mating type information regulation 2 homolog 1; TIMP1: tissue inhibitor of the matrix metalloproteinase 1; MMPs: matrix metalloproteinases significant extent since this enzymatic activity only operates in the picomole range compared to the liver that has very high conjugation levels, which has been discussed elsewhere. 18,39 It should be noted that phase I metabolism has been reported in intact human skin samples and comparisons have been made to in vitro skin models where, in general, the degree or levels of cytochrome 450 (CYP) and esterase activity are similar among the human epidermal/dermal layers and the 3D human skin models with epidermal components. [40][41][42][43] It is not known whether esterase activity via phase I metabolism played a role in the outcomes of the present study.…”
Section: Discussionmentioning
confidence: 99%